MATHEMATICAL CONNECTION OF ELEMENTARY SCHOOL STUDENTS TO SOLVE MATHEMATICAL PROBLEMS - Kenedi, Ary Kiswanto; Helsa, Yullys; Ariani, Yetti; Zainil, Melva; Hendri, Sherlyane (Journal on Mathematics Education, 2019)
This study aims to determine the mathematical connection ability of elementary school students in solving mathematical problems. This research uses the qualitative approach with descriptive method. We used observation, interview, and test to collect data. This study shows that 6.67% of the samples scored between 60 and 69 in the fair category. A total of 98 students or 81.67% scored between 45 and 59 who belonged to the below average category, and 14 students or 11.67% scored between 0 and 44 which were classified as a poor category. This result proves that the mathematical connection ability of elementary school students in solving mathematics problems is still low.